2008
DOI: 10.1080/19312430802213027
|View full text |Cite
|
Sign up to set email alerts
|

A Centralcasting Postmortem and a News-Share Projection: Using Market Theory to Assess Alternative Local Television News Strategies

Abstract: In the wake of decisions by two television station groups in 2006 to end centralcasting experiments, the author of this paper employed market theory to compare both centralcasting and contracted newscast products with traditional newscast products. Twenty-two newscasts that aired between 2004 and 2005 were recorded and analyzed in three southern markets. Results showed in the 2,583 stories analyzed there were more similarities than differences between the traditionally staffed local news operations and the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Smith, 2003) and was abandoned in 2006 (Romano, 2006). Daniels (2008) studied three markets that aired NewsCentral, comparing the newscasts with local stations in the same markets on several news attributes, including story location and type. The study found statistically significant differences between remotely delivered (News-Central) and locally produced newscasts on story location, with local newscasts carrying significantly more local stories and significantly fewer national/international stories.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith, 2003) and was abandoned in 2006 (Romano, 2006). Daniels (2008) studied three markets that aired NewsCentral, comparing the newscasts with local stations in the same markets on several news attributes, including story location and type. The study found statistically significant differences between remotely delivered (News-Central) and locally produced newscasts on story location, with local newscasts carrying significantly more local stories and significantly fewer national/international stories.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The first study (2007) detailed such incidents as the same remotely delivered newscast airing for hours on end, as well as remote newscasts emphasizing conflict stories over a major local celebration and missing major local stories such as a nearby forest fire. The second study (2010) included a content analysis of locally and remotely produced newscasts, with findings similar to Daniels (2008) and Mills and Daniels (2009): Many more local stories on locally produced newscasts, many more national and international stories on remotely produced programs. I later interviewed news workers involved with outsourcing, who described the challenges of producing newscasts for communities with which they were unfamiliar or had never visited (Hood, 2011).…”
Section: Background and Literature Reviewmentioning
confidence: 99%